A Cool Channel in Cold Transduction - Madrid-Montecinos, R (2011)
Transient receptor potential melastatin 8 (TRPM8), a calcium-permeable cation channel activated by cold, cooling compounds and voltage, is the main molecular entity responsible for detection of cold temperatures in the somatosensory system. Here, we review the biophysical properties, physiological role, and near-membrane trafficking of this exciting polymodal ion channel. © 2011 Int. Union Physiol. Sci./Am. Physiol. Soc.